Novel fusion genes and chimeric transcripts in ependymal tumors. Issue 12 (28th July 2016) - Olsen, Thale Kristin; Panagopoulos, Ioannis; Gorunova, Ludmila; Micci, Francesca; Andersen, Kristin; Kilen Andersen, Hege; Meling, Torstein R.; Due‐Tønnessen, Bernt; Scheie, David; Heim, Sverre; Brandal, Petter
Abstract : We have previously identified two ALK rearrangements in a subset of ependymal tumors using a combination of cytogenetic data and RNA sequencing. The aim of this study was to perform an unbiased search for fusion transcripts in our entire series of ependymal tumors. Fusion analysis was performed using the FusionCatcher algorithm on 12 RNA‐sequenced ependymal tumors. Candidate transcripts were prioritized based on the software's filtering and manual visualization using the BLAST (Basic Local Alignment Search Tool) and BLAT (BLAST‐like alignment tool) tools. Genomic and reverse transcriptase PCR with subsequent Sanger sequencing was used to validate the potential fusions. Fluorescent in situ hybridization (FISH) using locus‐specific probes was also performed. A total of 841 candidate chimeric transcripts were identified in the 12 tumors, with an average of 49 unique candidate fusions per tumor. After algorithmic and manual filtering, the final list consisted of 24 potential fusion events. Raw RNA‐seq read sequences and PCR validation supports two novel fusion genes: a reciprocal fusion gene involving UQCR10 and C1orf194 in an adult spinal ependymoma and a TSPAN4‐CD151 fusion gene in a pediatric infratentorial anaplastic ependymoma. Our previously reported ALK rearrangements and the RELA and YAP1 fusions found in supratentorial ependymomas were until now the only known fusion genes present in ependymal tumors. The chimeric transcripts presented here are the first to be reported in infratentorial or spinal ependymomas. Further studies are required to characterize the genomic rearrangements causing these fusion genes, as well as the frequency and functional importance of the fusions. © 2016 Wiley Periodicals, Inc.